Assessment of psychological dependence among tobacco users: A survey held among the rural population of India to call for attention of tobacco cessation centers - Kiran Jadhav; Dhanpal Singh (Wolters Kluwer Medknow Publications, 2013)
Background: In India most of the tobacco cessation centers are concentrating only on urban population, whereas, literature reveals that it is rural population, which shows high frequency of consumption of tobacco. It is well known that high frequency of tobacco consumption is associated with psychological dependence. This study aimed at identifying, which form of tobacco consumption (smoking or smokeless) is associated with psychological dependence and is associated with which particular age group in rural population. Materials and Methods: It was a questionnaire based survey where 200 subjects were enrolled. Revised version of standard Fagerstrom Test for Nicotine dependence (FTND) was given to each subject to answer. The collected data was statistically analyzed by using Karl Pearson Correlation (r) test and Student's t-test. Results: Study showed that subjects above 40 years of age are psychologically highly dependent on tobacco smoking as compared to tobacco chewing. Tobacco chewing is more prevalent among the younger population (20-30 years of age) and type of habit does not have any influence over psychological dependence below 40 years of age. A positive correlation was observed between duration of habit and psychological dependence in all age groups irrespective of type of the habit of tobacco consumption. Conclusion: This study attempts at creating a new avenue for the tobacco cessation centers where they can target their efforts towards rural population particularly people above 40 years of age with a tobacco smoking habit so that they can actually reduce the burden of a number of people at risk for developing tobacco associated oral cancer.